Multi-System Modeling Challenges for Integration of Parts for Increased Sustainability of Next Generation Aircraft - Johan Kos; Marie Moghadasi; Tim Koenis; Bram Noordman; Ozan Erartsin; Ruben Nahuis (Engineering Proceedings)
Innovative structures technologies can contribute to increasing the sustainability of next-generation aircraft. Advanced multi-disciplinary physics models, combined with data-based models, are needed to obtain optimized structures with maximum contributions to sustainability throughout the life cycle. Such models are needed for next-generation aircraft products, for better production of their parts, and for representative testing of their innovative systems. Modeling challenges addressed recently will be presented and illustrated in their industrial context. In particular, fast in-line detection of defects in large composite aircraft parts during their high-rate production, induction welding of thermoplastic carbon-fiber reinforced parts, and accurate design of composite fan blades for wind tunnel testing of fuel-efficient Ultra-High Bypass Ratio (UHBR) turbofan engines will be presented.